Concept for the treatment of Class III anomalies with a skeletally anchored appliance fabricated in the CAD/CAM process: the MIRA appliance - Hodecker, Lutz; Kühle, Reinald; Bouffleur, Frederic; Roser, Christoph; Lux, Christopher J.; Scheurer, Carolien A. J. (Bioengineering, 2023)
Objective: Intermaxillary elastics, anchored skeletally, represent a promising concept for treatment in adolescent patients with skeletal Class III anomalies. A challenge in existing concepts is the survival rate of the miniscrews in the mandible or the invasiveness of the bone anchors. A novel concept, the mandibular interradicular anchor (MIRA) appliance, for improving skeletal anchorage in the mandible, will be presented and discussed. Clinical case: In a ten-year-old female patient with a moderate skeletal Class III, the novel MIRA concept, combined with maxillary protraction, was applied. This involved the use of a CAD/CAM-fabricated indirect skeletal anchorage appliance in the mandible, with interradicularly placed miniscrews distal to each canine (MIRA appliance), and a hybrid hyrax in the maxilla with paramedian placed miniscrews. The modified alt-RAMEC protocol involved an intermittent weekly activation for five weeks. Class III elastics were worn for a period of seven months. This was followed by alignment with a multi-bracket appliance. Discussion: The cephalometric analysis before and after therapy shows an improvement of the Wits value (+3.8 mm), SNA (+5 degrees), and ANB (+3 degrees). Dentally, a transversal postdevelopment in the maxilla (+4 mm) and a labial tip of the maxillary (+3.4 degrees) and mandibular anterior teeth (+4.7 degrees) with gap formation is observed. Conclusion: The MIRA appliance represents a less invasive and esthetic alternative to the existing concepts, especially with two miniscrews in the mandible per side. In addition, MIRA can be selected for complex orthodontic tasks, such as molar uprighting and mesialization.